The Effect of the Economic Downturn on College Athletes and Athletic Departments on Issues of Diversity and Inclusion - Lapchick, Richard (Journal of Intercollegiate Sport, 2010)
In this paper I review the current and potential future effect of the economic downturn on matters of diversity and inclusion. I discuss reasons for cautious optimism in minority and female hiring patterns—both in the areas of athletic leadership and coaching. But this progress is uneven and tenuous. Special attention, I argue, is needed for the growing academic performance gap between white and African-American student athletes. Any economically-driven cuts in academic support and life skills education could exacerbate this problem. I conclude that the economic downturn, to date, does not appear to have had a major effect on diversity and inclusion. However, because periods of economic crisis typically have a greater negative impact on minorities than others, we need to carefully monitor athletic and academic programs from high school through college and continue to advocate for this “fragile ideal” of racial and gender equality.